Comparative Transcriptomics Atlases Reveals Different Gene Expression Pattern Related to Fusarium Wilt Disease Resistance and Susceptibility in Two Vernicia Species - Chen, Yicun; Yin, Hengfu; Gao, Ming; Zhu, Huiping; Zhang, Qiyan; Wang, Yangdong (Frontiers in Plant Science, 2016)
Vernicia fordii (tung oil tree) is a promising industrial crop. Unfortunately, the devastating Fusarium wilt disease has caused its great losses, while its sister species (Vernicia montana) is remarkably resistant to this pathogen. However, the genetic mechanisms underlying this difference remain largely unknown. We here generated comparative transcriptomic atlases for different stages of F. oxysporum infected Vernicia root. The transcriptomes of V. fordii and V. montana were assembled de novo and contained 258,430 and 245,240 non-redundant transcripts with N50 values of 1,776 and 2,452, respectively. A total of 44,310 pairs of putative one-to-one orthologous genes were identified in Vernicia species. Overall, the vast majority of orthologous genes shared a remarkably similar expression mode. The expression patterns of a small set of genes were further validated by quantitative real-time PCR. Moreover, 157 unigenes whose expression significantly correlated between the two species were defined, and gene set enrichment analysis indicated roles in increased defense response and in jasmonic and salicylic acid signaling responses during pathogen attack. Co-expression network analysis further identified the 17 hub unigenes, such as the serine/threonine protein kinase D6PK, leucine-rich repeat receptor-like kinase (LRR-RLK), and EREBP transcription factor, which play essential roles in plant pathogen resistance. Intriguingly, the expression of most hub genes differed significantly between V. montana and V. fordii. Based on our results, we propose a model to describe the major molecular reactions that underlie the defense responses of resistant V. montana to F. oxysporum. These data represent a crucial step towards breeding more pathogen-resistant V. fordii.